Path flow study of a lab scale cyclonic combustor for coal-biomass co-combustion - Ikram A.; Abd Rahman A.; Mostafa N.A.; Shamsuddin A.H. (2023)
A lab scale cyclonic combustor is in developmental stage for firing coal-biomass blends. The lab scale test rig would be used to support a study of coal-biomass co-combustion in a selected real pulverized coal, tangentially fired power plant. The conceptual design is made similar to the two-stage inverted cyclonic combustor at Cardiff University (A. Abd Rahman and N. Syred), previously used in a completed EU commissioned study on co-combustion. The design consists of two stages where the primary reactor is for fuel gasification and devolatilisation of volatile matters, followed by a secondary reactor for complete combustion of fuel. Cyclonic combustion is chosen as it can provide high turbulence during combustion, and the assumed flow path of particles mimics that of a real tangential boiler. The design would also allow the particle residence time to be in the same order to a real boiler. In order to better understand the cyclonic combustion process and optimize the rig operation, computational fluid dynamics (CFD) is used. At the current stage, CFD simulation of the flowpath is chosen to prove the subject as having a turbulence flow, before continuing with combustion simulation, and actual fabrication of the cyclonic combustor. 2009 IEEE.